(untitled) (Medico Legal Update, 2020)
A study to assess the Incidence and Associated Risk Factors of Urinary Tract Infection among children at selected tertiary care hospital, Kanchipuram District, Tamil Nadu. The objectives is to determine the incidence of UTI among children, estimate the types of bacteria causes UTI among children with UTI, to estimate the incidence of urinary tract infection among children.and find out the Association between the UTI and selected risk factors of children. The convenience sampling was used to 50 paediatric medical records from January 2017 to December 2018. The data collection tool was validated and reliability was established. The data were collected by structured questionnaire. The collected data was tabulated and analysed. Descriptive and Inferential Statistical method were used. The study shows that the higher frequency of 0-6 years (58%) and the lower frequency 13-18 years (18%). In Gender, Male is the highest frequency (56%) and Female is the lowest frequency(44%) and the history of birth defect of structure/deformity or blockage in one of the organ (20%), Vesico Ureteral Reflux (60%), Pelvic uretero junction (10%), Exstrophy of bladder system (10%). The highest frequency Vesicoureteral Reflux (60%) and the lowest frequency is Pelvic uretero junction (10%) and exstrophy of bladder system (10%). It is found that E.coli (86%), Klebsiella (10%), Proteus (2%), Pseudomonas (2%). The highest frequency E. Coli (86%) and the lowest frequency Proteus (2%), Pseudomonas (2%) most causative organism of UTI. The incidence rate for urinary tract infection in our study was 11.7%. There was a significant Association between the selected demographic variables and risk factors of UTI.